Comparing the variances or robust measures of scale of two dependent variables - Wilcox, Rand R. (Communications in statistics. Simulation and computation, 2022)
The paper deals with two issues. The first is testing the hypothesis that two dependent variables have a common variance. Currently, a heteroscedastic analog of the Morgan-Pitman test appears to perform relatively well. The paper demonstrates that when the marginal distributions differ in skewness, this method can be highly unsatisfactory. An explanation for this poor performance is provided. The second goal is to report simulation results on a percentile bootstrap method for comparing robust measures of scale. This approach was found to perform well in simulations, including the situation where the analog of the Morgan-Pitman test performs poorly.